Two-Dimensional Generalized Moment Representations and Rational Approximations of Functions of Two Variables - Holub, A. P.; Chernetska, L. O. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The Dzyadyk method of generalized moment representations is extended to the case of two-dimensional sequences and used to construct Padé approximants for functions of two variables.